Pneumatosis intestinalis in a patient with recurrent Clostridium difficile infection. (30th October 2012) - Ha, Duc; Tsai, Chung-Jyi
Abstract : A 65-year-old man with long-standing diarrhoea, recurrent Clostridium difficile infection (CDI) in the previous 5 months presented to the gastroenterology clinic with recurrent diarrhoea and abdominal cramping. Physical examination was negative for signs of acute abdomen. Stool C difficile PCR was positive. Abdominal imaging demonstrated an extensive pneumatosis intestinalis involving the small bowel and a dilated small bowel loop. He was treated conservatively with oral vancomycin for recurrent CDI with resolution of diarrhoea and abdominal cramping on 1-month follow-up visit.